2012
DOI: 10.1097/prs.0b013e318241285c
|View full text |Cite
|
Sign up to set email alerts
|

Breast Reconstruction Using a Staged Nipple-Sparing Mastectomy following Mastopexy or Reduction

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
120
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(131 citation statements)
references
References 26 publications
0
120
0
9
Order By: Relevance
“…According to the authors, the addition of the two staged incisions recreates the Wise pattern, breaking up the T point into two straightforward primary closures. Similarly, Spear et al [61] reported a successful two-stage NSM in 15 patients (24 breasts). All patients underwent NSM after mastopexy or reduction (71% prophylactic and 29% therapeutic) with an average follow-up of 13 mo.…”
Section: Two-stage Approachmentioning
confidence: 99%
See 4 more Smart Citations
“…According to the authors, the addition of the two staged incisions recreates the Wise pattern, breaking up the T point into two straightforward primary closures. Similarly, Spear et al [61] reported a successful two-stage NSM in 15 patients (24 breasts). All patients underwent NSM after mastopexy or reduction (71% prophylactic and 29% therapeutic) with an average follow-up of 13 mo.…”
Section: Two-stage Approachmentioning
confidence: 99%
“…Thus, the main objective in these sub-group of patients is to preserve the oncological objective of the NSM (therapeutic or risk reduction) while expanding the aesthetic outcome and minimizing complications. For this objective, some authors divided the onestage Wise-pattern skin excision into a two-stage procedure [61,63,64] . In the first stage, the mastopexy or reduction mammoplasty is performed, keeping periareolar dermis preserved to maintain the adequate NAC blood supply at the time of the future definitive NSM.…”
Section: Two-stage Approachmentioning
confidence: 99%
See 3 more Smart Citations